2022
DOI: 10.3389/fcvm.2022.899841
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lipids and Arterial Stiffness for Primary Cardiovascular Prevention in a General Middle-Aged European Population

Abstract: BackgroundDyslipidemia contributes to the progression of arterial stiffness (AS). The purpose of this study was to investigate the association of the different lipid parameters with arterial stiffness index (ASI) in a middle-aged population free of cardiovascular (CV) disease.MethodsAmong 71,326 volunteers from the UK Biobank population, total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), lipoprotein (a) [Lp(a)], apolipoproteins A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 64 publications
(64 reference statements)
4
12
1
1
Order By: Relevance
“…50 Several findings have shown that inflammation and dyslipidemia are correlated with increased arterial stiffness. [51][52][53] Dyslipidemia is closely associated to inflammation. Patients with dyslipidemia presented higher levels of inflammatory factors in comparison to normal participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Several findings have shown that inflammation and dyslipidemia are correlated with increased arterial stiffness. [51][52][53] Dyslipidemia is closely associated to inflammation. Patients with dyslipidemia presented higher levels of inflammatory factors in comparison to normal participants.…”
Section: Discussionmentioning
confidence: 99%
“…Several findings have shown that inflammation and dyslipidemia are correlated with increased arterial stiffness 51–53 . Dyslipidemia is closely associated to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…502,478 Britons aged of 40–70 years across 22 UK cities from the UK National Health Service Register were included between 2006 and 2010. The cohort was phenotyped and genotyped, with participants who responded to a questionnaire; a computer-assisted interview; physical and functional measures; and blood, urine, and saliva samples ( 62 64 ). Data included socio-economic status, lifestyle behaviors, a mental health battery, clinical diagnoses and therapies, genetics, imaging and physiologic biomarkers from blood and urine samples.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes status was defined on either receiving anti‐diabetic medication or diabetes diagnosed by a doctor or a fasting glucose concentration ≥7 mmol/L 33 . Dyslipidemia was defined as having a fasting plasma total‐cholesterol or triglycerides level of ≥6.61 mmol/L (255 mg/dL) or >1.7 mmol/L (150 mg/dL), respectively, or having statins medication 34 . Medications were characterized by the question: “Do you regularly take any of the following medications?”.…”
Section: Methodsmentioning
confidence: 99%